A new approach to data access and research transparency (DART) - Beugelsdijk, Sjoerd; van Witteloostuijn, Arjen; Meyer, Klaus E. (Journal of International Business Studies, 2020)
Recent debates on transparency and replicability suggest that JIBS needs to update its approach on data access and research transparency (DART). We propose a series of initiatives, knowing well that there is a balance to be struck. There are clear benefits on the one hand, chief among these the potential for learning and knowledge accumulation, and equally manifest challenges on the other: the imperative to respect privacy, confidentiality, and intellectual property rights. Without addressing these challenges, will there be the high-quality data on which the benefits depend? We present access and transparency objectives, and set out how an actionable and effective approach towards DART will be implemented, but also address ethical, legal, and organizational challenges of concern to us as a scholarly community.